2008
DOI: 10.1080/02701367.2008.10599518
|View full text |Cite
|
Sign up to set email alerts
|

Squat Jump Performance During Growth in Both Sexes

Abstract: The purpose of this cross-sectional study was to investigate leg muscle power and compare two activities (jumping and cycling) in 383 girls and 407 boys ages 9-19 years. Results in anthropometric characteristics and jumping performance were comparable until midadolescence, and sex differences were observed. Lean leg volume (LLV) was the reason for most of the variance (76% in girls and 88% in boys) in jumping performance. However the LLV exponent was higher than expected in boys but not girls. Therefore, unide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Although our study did not investigate coordination, D'Hondt et al [31] found an inverse correlation between motor coordination and lower mass in children of 5-10 years, and Stodden et al [35] reported that children with a higher level of motor coordination exhibit greater performance (explosive strength). In this sense, sex differences in lower limb power performance have been related to the expression of significant differences in fat-free mass [36]. Subsequently, changes in force production at the age of 13-14 years have been attributed to the dramatic increase in steroid concentrations in males [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not investigate coordination, D'Hondt et al [31] found an inverse correlation between motor coordination and lower mass in children of 5-10 years, and Stodden et al [35] reported that children with a higher level of motor coordination exhibit greater performance (explosive strength). In this sense, sex differences in lower limb power performance have been related to the expression of significant differences in fat-free mass [36]. Subsequently, changes in force production at the age of 13-14 years have been attributed to the dramatic increase in steroid concentrations in males [37].…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations have been found between maximal power on a cycle ergometre and vertical jump performances [105, 190194] and the stair case test of Margaria [191]. P max⁡ expressed per kilogram of body mass is significantly correlated with a squat jump (SJ) [192, 194] and a countermovement jump (CMJ) [105, 193].…”
Section: Correlation With Other Laboratory Testsmentioning
confidence: 99%
“…P max⁡ expressed per kilogram of body mass is significantly correlated with a squat jump (SJ) [192, 194] and a countermovement jump (CMJ) [105, 193]. However, the prediction of CMJ [105] or SJ [194] from P max⁡ is not accurate in spite of high correlation coefficients ( r = 0.87) [105, 192].…”
Section: Correlation With Other Laboratory Testsmentioning
confidence: 99%
See 2 more Smart Citations